Forearm vasodilatation to a β2‐adrenergic receptor agonist in premenopausal and postmenopausal women. Issue 5 (16th April 2020) - Harvey, Ronée E.; Ranadive, Sushant M.; Limberg, Jacqueline K.; Baker, Sarah E.; Nicholson, Wayne T.; Curry, Timothy B.; Barnes, Jill N.; Joyner, Michael J.
Abstract : New Findings: What is the central question of this study? What is the role of β2 ‐adrenergic receptor (β2 AR) vasodilatation in older postmenopausal women as compared to premenopausal women and the role of nitric oxide (NO) in β2 AR‐mediated vasodilatation in both groups of women? What is the main finding and its importance? β2 AR responsiveness is blunted in postmenopausal women compared to young premenopausal women. Additionally, NO may contribute to β2 AR‐mediated vasodilatation in young premenopausal women. Abstract: β2 ‐Adrenergic receptor (β2 AR)‐mediated vasodilatation, which is partially dependent on nitric oxide (NO) formation, is blunted in men at risk for developing hypertension. However, the role of β2 AR vasodilatation in hypertension pathophysiology in ageing postmenopausal women is unclear. Therefore, the goals of this study were to determine if forearm vasodilatation to the selective β2 AR agonist terbutaline is blunted in older postmenopausal women (59 ± 4 years) compared to young premenopausal women (27 ± 3 years) and to assess NO contribution to β2 AR‐mediated vasodilatation in both groups of women. Forearm blood flow (FBF) and forearm vascular conductance (FVC) were measured using venous occlusion plethysmography at baseline and during intra‐arterial infusions of terbutaline at 0.1–2.0 µg (100 ml tissue) −1  min −1 with and without the NO synthase inhibitor l ‐ N G ‐monomethylarginine (l ‐NMMA). Mean arterial pressure was significantly greater in postmenopausal women than in young women at baseline ( P  = 0.01). Baseline FBF and FVC did not differ between young and postmenopausal women ( P  > 0.05) and rose significantly within each group during terbutaline infusion ( P  < 0.05). There were significant group × dose interactions for FBF ( P  = 0.01) and FVC ( P  = 0.001), indicating vasodilator responses were lower in postmenopausal women. In young women, FVC response to the highest dose of terbutaline tended to be lower with l ‐NMMA co‐infusion vs . without l ‐NMMA ( P  = 0.05). There were no significant decreases in FBF or FVC responses to terbutaline in postmenopausal women with l ‐NMMA co‐infusion ( P  > 0.05 for all). These data suggest that β2 AR responsiveness is blunted in postmenopausal women compared to young premenopausal women, and that NO may contribute to β2 AR‐mediated vasodilatation in young premenopausal women. Abstract :